Manufacturing Reliability Assessment of Fine Ag Alloy Wire During Wire Loop Formation Process - Deshin Liu; Tingsheng Chang; Zhenwei Zhuang; Yungching Chao; Sungting Chung; Peichen Huang (IEEE Access)
In present study, the thermo-mechanical responses of Ag alloy wire during wire bonding manufacture procedure is analyzed by the combined experimental and simulation approach. A micro-tensile test method is adopted to investigate the temperature and strain rate dependence mechanical properties of Ag alloy wire. Extracted stress-strain curves are further utilized to demonstrate the coupled thermo-mechanical response via the utilization of Johnson-Cook (J-C) constitutive model. Aforementioned constitutive model is imported into transient dynamic simulation to estimate the characteristics on wire loop formation profile and wire stress distribution. Under the different consideration of wire loop formation speed, it is found that the strain rate has significant influence on plastic strain and corresponding stress at kink region, which is interpolated by the J-C model. The critical stress/strain location and loop height of concerned wire can be effectively estimated by the present approach, and provided the design guidelines of fine Ag alloy wire in application of electronic packaging.